N4: On assessing and anticipating consequences of innovation - Awulachew, Seleshi Bekele; McCartney, Matthew P.; Hagos, Fitsum; Mapedza, Everisto D.; Seyoum, Solomon; Erkossa, Teklu (2010)
This project is about showing whether RMSs are effective. It will seek to quantify the consequences of improved RMS for community livelihoods, resource productivity, land quality, and downstream water quality and siltation. It will specifically measure the downstream, cross-scale consequences of successful innovation in the Ethiopian highlands. This project will develop methods to anticipate ex ante the likely consequences of introducing improved RMS as well as monitoring and measuring these consequences ex post. Finally, it will introduce methods for adaptive management. Assessing and anticipating the consequences of improved RMS will cover a range of variables, among them water allocation, land and water use practices, community infrastructure, water productivity, farm income, livelihoods resilience and ecosystem services.